About some questions of differentiation of jurisdiction of civil and eco-nomic cases at the present stage of development of the legal system of the Republic of Belarus - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2020)
The article examines the delimitation of the competence of civil courts and economic courts after the reform of the judiciary of 2013–2014. The author concludes that the delimitation of competence between those and other courts is currently a matter of jurisdiction, but the rules on substantive competence should be guided in solving this issue. Failure to comply with these rules should entail consequences related to the violation of jurisdiction, except for transferring the case to another court. Based on the results of the study, proposals were made to improve legislation and the practice of its application.
Keywords: courts of general jurisdiction; courts of economic competence; courts of non-economic competence; rules of substantive competence; rules of jurisdiction